Trifluralin Impacts Soil Microbial Community and Functions - Li, Shuang; Du, Pengqiang; Wu, Xiaohu; He, Hairong; Zhou, Lin; Dong, Fengshou; Liu, Xingang; Zheng, Yongquan (Frontiers in Environmental Science, 2022)
A 3-month experiment was designed to research the impact of trifluralin (TFL) on soil microbial communities and functions under the condition of greenhouse. In this work, silty loam from Langfang was treated with three doses of TFL (1260 g ha-1, 12600 g ha-1, 126000 g ha-1) and incubated for 90 days. The halflives of TFL were 15–23 d in all cases. The bacterial and fungal diversities and community structures were impacted by TFL. The bacterial functions of chemoheterotrophy and sulfur oxidation were decreased shortly, but the hydrocarbon degradation ability was significantly increased in the results of functional annotation of prokaryotic taxa (FAPROTAX). For the predicted results of TAX4FUN, amino acid (arginine and proline) metabolism and ABC transporter were decreased significantly, while nitrogen metabolism and ribosome translation were significantly increased. In conclusion, this work aids us to understand the risk of TFL in soil more comprehensive.